Kelam Kehidupan Melalui Karya Tari Sesal - Afriyani, Dita (Jurnal Pendidikan Tari, 2021)
Sesal dance work aimed to convey the remorse of the Dangdut singer on stage with erotic shakes, slashing, and the bad views of the community that are poured into a dance work to fulfill the requirements for the Strata-1 exam for Dance Education Study Program, Jakarta State University. In addition to meeting the requirements for the final project. The method used in the Sesal dance work uses the Alma M Hawkins creation method entitled Moving from Within: A New Method for Dance Making and is translated by I Wayan Dibia in his book entitled Moving According to the Heart. Data collection techniques using interview techniques, observation and literature study. This dance creation is staged indoors by setting a black backdrop and supporting lighting because the creation of dance works was carried out during the Covid-19 pandemic. Sesal Dance has a duration of 15 minutes with 5 scenes. The movements produced in the works developed from Betawi traditional movements into new creations that are in accordance with the theme. In the creation of this dance work involves 2 dancers, where both of them become the same main character of the songstress so that the message to be conveyed in this dance work is realized.